DUKUNGAN KELUARGA DENGAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA - Supatmi Supatmi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
The incidence of breast cancer is a serious health problem in the world, including in Indonesia. Many cases of breast cancer are found in end-stage women, due to a lack of adequate diagnosis, treatment and facilities. The Indonesian Ministry of Health said that one of the reasons for the growing development of cancer is the low coverage of breast cancer early detection behavior. Cancers that are caught early have the possibility to get better treatment. Breast cancer can be found early with breast self-examination (BSE). The purpose of this study was to determine the relationship between parental support and knowledge and attitudes of breast self-examination (BSE) in MA Al-Ishlah Dasuk-Sumenep students. The research method used in this study is correlation analysis with a cross sectional approach, the population in this study were all students of MA-AL Ishlah Dasuk with saturated sampling technique. The independent variable for parental support and the dependent variable is breast self-examination behavior. Data were collected using a questionnaire. The data were analyzed using the Spearmen Rank (rho) statistical test with a significance value of a = 0.05. There was a correlation between parental support and breast self-exam- ination behavior (knowledge and attitude) with a P value of 0.00 <0.05 with a coefficients correlation of 7.31, while family support with an attitude of P value 0.00 <0.05 with a coefficient correlation - 631. The conclusion of this study is that there is a significant relationship between parental support for self-examination (BSE).